Pemetaani Bibliometriki terhadapi Perkembangani Penelitiani Auditi Oprasionali Menggunakani VOSviewer - Ahmadi Sorip; Bondan Wirajaya; Carmeli Meiden (AKUNTANSI 45, 2024)
Accounting research and the use of operational auditing aims to trigger a signal that lies in the growth of the field of accounting research. Interpreting and explaining operational auditing and its use in the development of accounting research is the aim of this research. and the interaction phenomena of accountants as a result of this research.i Therefore, accounting research cannot be separated into subjects and objects of research. This research.i The literature review in this research provides insight into the application of operational auditing.i This study takes articles about operational auditing from 2017 to 2022. In 2019, there were 32 articles and the country that published the most operational audit articles was Indonesia. provide recommendations for further research. i Proposal for additional research, i search engines other than Google, i Scholar, i can add, i Scorpusi and other tools, i can add, i and the research period is 20 years